Annual Report of the Park Commissioners of the City of Lynn for the Year Ending December 20, 1892, at 45 (1893) - (:unkn) unknown (My University, 1892)
Prohibited discharge or carry of firearms, except for members of the police force.
Keywords: CARRY; DISCHARGE